Promising practices connecting schools to families of children with special needs - Hiatt-Michael, Diana B. (Emerald Publishing Limited : Information Age Pub., 2004)
Focusing on parent involvement in children's education in the USA, this volume covers such topics as: government support; parent-school communication; parent-child literacy projects; preparation for teachers; and parent centres.
Keywords: Children with disabilities -- Education -- United States.; Special education -- Parent participation -- United States.; Home and school -- United States.; Community and school -- United States.; Education -- Special Education -- General.; Teaching of students with different educational needs.; elektronické knihy; electronic books